2004
DOI: 10.1093/toxsci/kfi022
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone Proteins Involved in Troglitazone-Induced Toxicity in Human Hepatoma Cell Lines

Abstract: Troglitazone (TRO), an effective thiazolidinedione antidiabetic agent, was reported to produce idiosyncratic hepatotoxic effects in some individuals. In contrast, rosiglitazone (RSG), in the same group of agents, has no significant toxic effects and now is widely used. In this study, human hepatoma (HepG2) cell lines were exposed to various doses of TRO as well as RSG (0, 25, 50, and 75 microM) for 48 h. Cell lysates were separated by two-dimensional electrophoresis, and the gels were stained with coomassie br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
(42 reference statements)
0
19
0
Order By: Relevance
“…Induction of these endoplasmic reticulum chaperones is crucial for cell survival by re-establishing correct folding of proteins, preventing their aggregation and ultimately protecting cancer cells against endoplasmic reticulum stress-induced apoptosis (14,15). GRP78 expression was reported to be induced in a variety of human solid tumors (16)(17)(18)(19)(20)(21)(22)(23), whereas its expression in hematologic malignancies has not been investigated thus far. Here, we observed that malignant cells from AML patients with activated unfolded protein response expressed higher GRP78 and CHOP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of these endoplasmic reticulum chaperones is crucial for cell survival by re-establishing correct folding of proteins, preventing their aggregation and ultimately protecting cancer cells against endoplasmic reticulum stress-induced apoptosis (14,15). GRP78 expression was reported to be induced in a variety of human solid tumors (16)(17)(18)(19)(20)(21)(22)(23), whereas its expression in hematologic malignancies has not been investigated thus far. Here, we observed that malignant cells from AML patients with activated unfolded protein response expressed higher GRP78 and CHOP levels.…”
Section: Discussionmentioning
confidence: 99%
“…The attenuation of protein synthesis is one hallmark of UPR activation, as ER stress stimulates eIF2␣ phosphorylation, resulting in a translational blockade (21)(22)(23). It has now been reported in a number of cell types that PGJ 2 is capable of stimulating the expression of ER stress-responsive genes such as CHOP and glucose-regulated protein 78 (BiP), the phosphorylation of eIF2␣, and the attenuation of translation (19,38,48,55).…”
Section: Discussionmentioning
confidence: 99%
“…This results in the accumulation of incompletely folded proteins and activates the transcription of ER chaperone genes (Liu et al 1998;Lodish and Kong 1990). We found that troglitazone treatment of hepatoma cell lines led to overexpression of immunoglobulin heavy chain binding protein (BiP), an abundant chaperone protein in the ER (Maniratanachote et al 2005a). The important role of this chaperone protein was indicated by the phenotypic change in cell viability when BiP expression was inhibited by small interference RNA (Maniratanachote et al 2005a).…”
Section: Protein Translation-associated Toxicitymentioning
confidence: 99%